Pilomatrixoma of eyelid in a middle aged - Passi, N; Chawla, U; Joyti, A; Khurana, AK (Nepalese Journal of Ophthalmology, 2011)
Background: Pilomatrixoma , also known as Malherbes’s calcifying epithelioma, known to occur in children, is not common especially in middle aged and those below 10 years of age . Pilomatrixoma presents as a firm skin nodule on eye lid or eye brow, so should be considered in the differential diagnosis of such lesions involving eyelids. Case: A 45-year-old male presented with a swelling in the left upper lid for the last 4 months. There was firm to hard non tender nodule measuring 1.5 cm. x 1.5cm in size on the lateral aspect of the left upper eye lid , involving the lid margin with variegated appearance of overlying skin with a few ulcerated areas on the surface. A presumptive diagnosis of meibomian gland carcinoma was made and an excision biopsy with primary lid repair was carried out. Histopathological examination confirmed the diagnosis of pilomatrixoma. Conclusion: The present case is reported to sensitize the ophthalmologists to think beyond chalazion and meibomian gland carcinoma for a firm, nodular, non ulcerated, painless lid swelling. Key words: Pilomatrixoma; Malherbes’s calcifying epithelioma; eyelid nodule DOI: 10.3126/nepjoph.v3i1.4286 Nepal J Ophthalmol 2011;3(5):88-90